A novel CTBP1 variant in a Chinese pediatric patient with a phenotype distinct from hypotonia, ataxia, developmental delay, and tooth enamel defect syndrome - Zhang, Qiang; Liu, Yusi; Liu, Xuan; Zhao, Yue; Zhang, Jihong (Frontiers in Genetics, 2024)
Hypotonia, Ataxia, Developmental Delay, and Tooth Enamel Defect Syndrome (HADDTS) is an exceptionally rare disorder resulting from a heterozygous variant in the C-terminal binding protein 1 (CTBP1) gene. To date, a mere two variants (14 patients) have been documented on a global scale. The aim of this study was to identify a causative CTBP1 variant in a Chinese patient, and to determine the potential pathogenicity of the identified variant. Here, Whole-exome sequencing (WES) was conducted on the proband to pinpoint the candidate variant. Following this, Sanger sequencing was employed to validate the identified candidate variant and examine its co-segregation within the available family members. Employing both in silico prediction and three-dimensional protein modeling, we conducted an analysis to assess the potential functional implications of the variant on the encoded protein. Our investigation led to the identification of a novel heterozygous variant in the CTBP1 gene, namely, c.371 C>T (p.Ser124Phe), in a Chinese patient. This case represents the first confirmed instance of such a variant in a Chinese patient. When comparing the patient’s clinical symptoms with those reported in the literature, notable distinctions were observed between her primary symptoms and those associated with HADDTS. She showed other signs such as microcephaly, coarse facial features, single transverse palmar crease, visible beard, myopia, coarse toenail and skeletal anomalies. This study enriching the spectrum of genetic variants observed in different ethnic populations and expanding the phenotypic profile associated with this gene. These findings are expected to contribute to the enhancement of future variant-based screening and genetic diagnosis, while also providing further insights into the pathogenic mechanisms underlying CTBP1-related conditions.